2021
DOI: 10.3389/fpubh.2021.658649
|View full text |Cite
|
Sign up to set email alerts
|

Income, Relative Deprivation and the Self-Rated Health of Older People in Urban and Rural China

Abstract: Background: Substantial evidence indicated that absolute income is directly associated with health. Few studies have, however, examined if relative income may be equally associated with health. This study aimed to investigate the association between absolute income/relative deprivation (RD) and self-rated health (SRH). We also investigated whether the urban-rural difference was existing in these associations.Methods: Using cross-sectional data of 7,070 participants in the Shandong Family Health Service Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
2
20
0
1
Order By: Relevance
“…As fears grow about the burden of government finance, the establishment of a reasonable individual-social-government payment mechanism might be essential 43 . The relative deprivation may have a greater negative impact on older rural people, which could explain the finding that poorer health status was associated with low income 44 . Moreover, low income further resulted in older rural adults acquiring less individual social capital, thus affecting their health-related quality of life 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As fears grow about the burden of government finance, the establishment of a reasonable individual-social-government payment mechanism might be essential 43 . The relative deprivation may have a greater negative impact on older rural people, which could explain the finding that poorer health status was associated with low income 44 . Moreover, low income further resulted in older rural adults acquiring less individual social capital, thus affecting their health-related quality of life 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The existing empirical studies in China revealed that subjective SES was highly related to health. Invidious upward social comparisons would lead to perceived relative deprivation, which is negatively associated with self-rated health in both urban and rural older people [ 52 ]. Current studies based on a large-scale survey, such as China Family Panel Studies, also showed that subjective social status was correlated with health, personal relative deprivation had negative effects on the health of the Chinese population, and individuals with high expected mobility were found to have significantly better health [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative deprivation has already threatened political trust [ 60 ]. The lower the income of the elderly, the more difficult it is to meet their own needs, and they are more likely to be in a disadvantaged position when making social comparisons with others, resulting in relative deprivation [ 52 ]. The results of our research implied that lower self-rated SES and upward mobility of the elderly might signal a sense of relative deprivation, which contributed to the low trust in the health system.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature suggests that income plays a significant role in the mental health of households (Duong & Bradshaw, 2016; Qin et al, 2021; Shields‐Zeeman et al, 2021). Households with lower income are more likely to have poor health.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Subjective wellbeing is considered a dimension of mental health (Jans‐Beken et al, 2018; Keyes, 2005; Westerhof & Keyes, 2010). Literature suggests that farmers’ mental health is affected by household income (Duong & Bradshaw, 2016; Qin et al, 2021; Shields‐Zeeman et al, 2021) and social capital (Akaeda, 2021; Fiorillo et al, 2020; Lin et al, 2019), as well as the farming (agricultural) work environment, including financial instability, isolation and chemical exposure (Fraser et al, 2005; Judd et al, 2006). In addition, supplemental off‐farm employment is also associated with higher levels of mental distress (Logstein, 2016).…”
Section: Introductionmentioning
confidence: 99%